Relation of complementary foods and anemia in urban underprivileged children in Surakarta - Endang Dewi Lestari; Annang Giri Moelya; Elief Rohana; Budiyanti Wiboworini (Paediatrica Indonesiana, 2007)
Background Iron deficiency anemia (IDA) is still prevalent inIndonesian children. Attempt to treat patients with IDA withiron supplementation has been difficult because of lowcompliance.Objective To determine the complementary foods that contributesin the prevalence of anemia in children.Methods A cross sectional study was conducted in three urbanunderprivileged villages. Healthy children aged 6-23 months atthe time of interview were selected. The questionnaire wasspecially developed for determining the risks of IDA. We tookblood sampling to measure the hemoglobin concentration.Results A total of 86 children participated in the study; but only dataof 78 children were available for analysis. The prevalence of anemiaamong those children was 35%. Most children (90%) consumedanimal protein inadequately. Rice-based diet was the main meal ofmost children (97%). Analysis of possible factors associated with theanemia showed that inadequate plant or animal protein consumption,wasted children, less than 2 orange consumption, not consumingiron fortified formula/cereal had OR 1.2 (95%CI 0.40; 3.61), 4.13(95%CI 0.48;35.45), 4.67 (95%CI 1.04;20.04), 6.25 (95% CI1.32;29.55) and 3.15 (95%CI 1.18;8.41), respectively. Logistic analysisrevealed that the factors associated with anemia were wasted children(OR 9.10, 95%CI 1.38;60.18), low or no orange consumption (OR7.86, 95%CI 1.36;45.40) and not consuming iron fortified formula/cereal (OR 3.01, 95%CI 1.02;8.90).Conclusion In children with rice-based diet as main meal,consuming orange as an enhancing factor should also be addressedin order to prevent anemia.